The Impact of Sleep and Circadian Disturbance on Hormones and Metabolism. (11th March 2015) - Kim, Tae Won; Jeong, Jong-Hyun; Hong, Seung-Chul
Abstract : The levels of several hormones fluctuate according to the light and dark cycle and are also affected by sleep, feeding, and general behavior. The regulation and metabolism of several hormones are influenced by interactions between the effects of sleep and the intrinsic circadian system; growth hormone, melatonin, cortisol, leptin, and ghrelin levels are highly correlated with sleep and circadian rhythmicity. There are also endogenous circadian mechanisms that serve to regulate glucose metabolism and similar rhythms pertaining to lipid metabolism, regulated through the actions of various clock genes. Sleep disturbance, which negatively impacts hormonal rhythms and metabolism, is also associated with obesity, insulin insensitivity, diabetes, hormonal imbalance, and appetite dysregulation. Circadian disruption, typically induced by shift work, may negatively impact health due to impaired glucose and lipid homeostasis, reversed melatonin and cortisol rhythms, and loss of clock gene rhythmicity.